Anteseden pemanfaatan insentif PPh final UMKM di masa pandemi - Usman Nur Hamzah (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2022)
The utilization of tax incentives, especially the incentive of final income tax of small and medium enterprises (SMEs) still low from the predetermined allocation. This study analyzes the factors influencing the utilization of SMEs' final income tax incentives during the covid-19 pandemic. This study was conducted by distributing questionnaires to SME taxpayers in the KPP Pratama Probolinggo working area. The data analysis method uses structural equation modeling (SEM) with 147 respondents as the research sample. The results showed that taxpayers' knowledge about the SMEs' final income tax incentives significantly affected the intention to apply the incentives. Besides that, the socialization of the SMEs' final income tax incentives substantially affects the choice to use the incentives through knowledge. Perceived value and financial condition do not significantly affect the intention to apply the incentives. Educational socialization about SMEs' final income tax incentives needs to be carried out effectively so taxpayer knowledge is formed and can further increase the intention to take advantage of MSME final tax incentives.AbstrakPemanfaatan insentif PPh final UMKM dinilai masih rendah dari alokasi yang telah ditetapkan. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi pemanfaatan insentif PPh final UMKM di masa pandemi covid-19. Penelitian ini dilakukan dengan menyebarkan kuesioner kepada Wajib Pajak UMKM di wilayah kerja KPP Pratama Probolinggo. Hasil penelitian menunjukkan bahwa pengetahuan Wajib Pajak tentang insentif PPh final UMKM berpengaruh signifikan terhadap minat pemanfaatan insentif. Sosialisasi insentif PPh final UMKM juga berpengaruh signifikan terhadap minat pemanfaatan insentif melalui pengetahuan. Selain itu, persepsi nilai dan kondisi keuangan tidak berpengaruh signifikan terhadap minat pemanfaatan insentif. Sosialisasi yang bersifat edukasi tentang insentif PPh final UMKM perlu dilakukan secara efektif sehingga terbentuk pengetahuan Wajib Pajak dan selanjutnya dapat meningkatkan minat untuk memanfaatkan insentif PPh final UMKM.